Ring Oscillator PUF on FPGA: Design and Characterisation by Using Second-Order Compensated Measurement - Fernández Aragón, Jorge; Diez-Senorans, Guillermo; Garcia-Bosque, Miguel; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2022)
Physically unclonable functions (PUFs) have become an important area of study in the field of hardware security. In this paper we will design ring oscillator PUFs implemented in FPGAs and characterise them using a new concept: second-order compensated measurement by two-bit extraction.